2020
DOI: 10.1111/hel.12717
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole‐amoxicillin dual therapy as first‐line treatment for H pylori eradication in special patients: A retrospective, real‐life study

Abstract: Background The currently recommended quadruple regimens for Helicobacter pylori infection might not be appropriate for every patient, especially in elderly patients or those with multiple comorbidities. Objective To evaluate the efficacy and safety of rabeprazole‐amoxicillin dual therapy in H pylori‐positive elderly patients or those with multiple comorbidities. Methods From November 2013 to May 2017, the clinical data of H pylori‐positive patients ≥60 years old or with multiple comorbidities were collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Susceptibility based first‐line treatments have been demonstrated to be superior to empiric ones and prevent patients from intake of already inefficient antimicrobials 10 . If there is no opportunity to have susceptibility tested, physicians need to consider eradication treatments that are largely independent of resistances such as quadruple therapies including metronidazole, tetracycline, bismuth salt and PPI or dual therapies with amoxicillin and PPI 26‐29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility based first‐line treatments have been demonstrated to be superior to empiric ones and prevent patients from intake of already inefficient antimicrobials 10 . If there is no opportunity to have susceptibility tested, physicians need to consider eradication treatments that are largely independent of resistances such as quadruple therapies including metronidazole, tetracycline, bismuth salt and PPI or dual therapies with amoxicillin and PPI 26‐29 …”
Section: Discussionmentioning
confidence: 99%
“…10 If there is no opportunity to have susceptibility tested, physicians need to consider eradication treatments that are largely independent of resistances such as quadruple therapies including metronidazole, tetracycline, bismuth salt and PPI or dual therapies with amoxicillin and PPI. [26][27][28][29]…”
Section: Ta B L E 1 Baseline Data Of Study Patientsmentioning
confidence: 99%
“…A systematic review and meta-analysis indicated that the efficacy and compliance of modified dual therapy was comparable with the current mainstream first-line regimens for H. pylori infection, with a significantly lower incidence of adverse side effects ( 120 , 121 ). A retrospective, real-life study demonstrated that modified dual therapy consisting of high-dose amoxicillin and rabeprazole was effective and safe for the first-line treatment of H. pylori infection in elderly patients ( 122 ). Although the dosage and frequency are increased in modified dual therapy, the total dose throughout the day remains within the safe range.…”
Section: Treatmentmentioning
confidence: 99%
“…with high rates of corpus gastritis) and typically has required high doses of PPIs as measured in omeprazole equivalents. Recent studies in Asia where CYP2C19 rapid metabolizers are uncommon, parietal masses are low, and corpus gastritis is common to have shown that high‐dose PPI–amoxicillin can produce cure rates around 90% 16–23 . The effectiveness of the regimen is sensitive to factors such as total dose of amoxicillin, the frequency of amoxicillin and antisecretory drug administration, the duration/24‐h intragastric pH is maintained ≥6, and the duration of therapy.…”
Section: Vonoprazan–amoxicillin Dual Therapymentioning
confidence: 99%
“…Recent studies in Asia where CYP2C19 rapid metabolizers are uncommon, parietal masses are low, and corpus gastritis is common to have shown that high-dose PPI-amoxicillin can produce cure rates around 90%. [16][17][18][19][20][21][22][23] The effectiveness of the regimen is sensitive to factors such as total dose of amoxicillin, the frequency of amoxicillin and antisecretory drug administration, the duration/24-h intragastric pH is maintained ≥6, and the duration of therapy. Trials with PPIs suggested that 3 g of amoxicillin per day, a high potency PPI b.i.d., and duration of 14 days have proved effective.…”
Section: Vonoprazan-amoxicillin Dual Therapymentioning
confidence: 99%